Initiatives and partnerships in an Australian metropolitan obesity prevention system: a social network analysis - Blackford, Krysten; Leavy, Justine; Vidler, Abbie-Clare; Chamberlain, D.; Pollard, Christina; Riley, T.; Milligan, M.; Jancey, Jonine (BMC, 2021)
Background: Limited resources make prevention of complex population-level issues such as obesity increasingly challenging. Collaboration and partnerships between organisations operating in the same system can assist, however, there is a paucity of research into how relationships function at a local level. The aim of this study was to audit initiatives, explore networks, and identify potential opportunities for improving the obesity prevention system in a Health Service area of Western Australia (WA).